Lending structure and 3-factor CAPM risk exposures: the case of Malaysia (Struktur pinjaman dan pendedahan risiko bagi 3-Faktor CAPM: kajian kes di Malaysia) - Abdul Rahman, Aisyah; Ibrahim, Mansor; Mydin Meera, Ahamed Kameel (Universiti Kebangsaan Malaysia, 2010)
This study addresses the linkages between lending structure and bank risk exposures via the Capital Asset Pricing Model (CAPM). Based on the 3-factor CAPM, five risk measures are examined; namely, the market, interest rate, exchange rate, total and unsystematic risk exposure. The influence of lending structure is analysed via four measures, the real estate lending, the specialisation index, the short-term lending stability, and the medium-term lending stability. Our findings show that the lending structure affects the market, interest rate, and unsystematic risk exposures. The stability of lending structure in both the short-term and medium-term period positively influence the market and interest rate risk exposure. On the other hand, the medium-term lending structure stability negatively affects the unsystematic risk exposure. Thus, the policy makers, bankers, and investors should not ignore the significant role of the lending structure when developing a strategic risk management framework.